1993
DOI: 10.1085/jgp.101.5.695
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of a sustained calcium current by intracellular pH in horizontal cells of fish retina.

Abstract: A B S T R AC T A sustained high voltage-activated (HVA), nifedipine-and cadmiumsensitive calcium current and a sustained calcium action potential (AP) were recorded from horizontal cells isolated from catfish retina, pH indicator dyes showed that superfusion with NH4CI alkalinized these cells and that washout of NH4C1 or superfusion with Na-acetate acidified them. HVA current was slightly enhanced during superfusion of NH4C1 but was suppressed upon NH4C1 washout or application of Na-acetate. When 25 mM HEPES w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 47 publications
(68 reference statements)
3
37
0
Order By: Relevance
“…In contrast, the effects of NH 3 and TMeA to increase the magnitudes of depolarization-evoked Ca 2+ potentials, [Ca 2+ ] i transients and I Ca were attenuated by increasing b T . Although these findings are consistent with reports that increases in pH i augment Ca 2+ influx via high-voltage-activated Ca 2+ channels [23,28,47,50], the attenuation of the enhanced Ca 2+ influx by high b T was not complete. This may in part reflect the inability of 100 mM internal tricine to abolish the rise in pH i evoked by a high concentration of TMeA, although effects independent from increases in pH i also likely contribute.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In contrast, the effects of NH 3 and TMeA to increase the magnitudes of depolarization-evoked Ca 2+ potentials, [Ca 2+ ] i transients and I Ca were attenuated by increasing b T . Although these findings are consistent with reports that increases in pH i augment Ca 2+ influx via high-voltage-activated Ca 2+ channels [23,28,47,50], the attenuation of the enhanced Ca 2+ influx by high b T was not complete. This may in part reflect the inability of 100 mM internal tricine to abolish the rise in pH i evoked by a high concentration of TMeA, although effects independent from increases in pH i also likely contribute.…”
Section: Discussionsupporting
confidence: 90%
“…An additional possibility is that weak-base-induced increases in Ca 2+ influx could in part reflect the inhibition of the medium and slow AHPs, which normally act as a negative feedback mechanism to regulate Ca 2+ influx [11,13,16,30]. This could also provide an explanation for previous findings that externally applied weak bases have a greater effect to augment Ca 2+ -dependent depolarizing potentials (evoked under conditions where AHPs were not blocked) than I Ca (evoked under conditions where all K + currents were blocked) [47] (see also [50]). Inhibition of mI AHP and sI AHP , with a consequent increase in Ca 2+ influx and decrease in K + efflux, may also contribute to the development of the ADPs occasionally seen in the presence of NH 3 or TMeA [36,56,57].…”
Section: Discussionmentioning
confidence: 89%
“…6(B) yields an intrinsic β i value at the horizontal cell's resting pH i of 24n2 m\pH unit. This value is within the range of measurements that have been made in neurons from a variety of invertebrates, 9-33 m\pH unit (Chesler, 1990), and not much higher than the intrinsic buffer capacity (10-15 m\pH) estimated in catfish horizontal cells (Dixon et al, 1993).…”
Section: Intracellular Buffering Capacitysupporting
confidence: 69%
“…For example, experimentally-induced changes in extracellular pH have been shown to modify synaptic transmission from photoreceptors to second-order neurons (Barnes, Merchant and Mahmud, 1993 ;Harsanyi and Mangel, 1993), and recent evidence indicates that -glutamate, the neurotransmitter released by vertebrate photoreceptors, raises the intracellular proton concentration of catfish horizontal cells (Dixon, Takahashi and Copenhagen, 1993). The resultant acidification has been shown to suppress the high voltage-activated calcium current of these second-order neurons (Takahashi, Dixon and Copenhagen, 1993), which can, in turn, affect both the membrane potential and the calcium-dependent process of transmitter release. On the other hand, a voltage-dependent inwardly-rectifying K + current was found to be relatively insensitive to acidification, but alkalinization shifted the activation range and greatly enhanced the current responses induced by hyperpolarizing voltage steps (Takahashi and Copenhagen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the sensitivity of I Ca to extracellular pH, studies of L-type calcium channels in other retinal neurons suggest that intracellular pH can modulate photoreceptor Ca 2+ channels as well. Takahashi et al (115) showed that intracellular alkalinization and acidification of catfish horizontal cells enhanced and reduced, respectively, L-type calcium currents. It is very plausible to assume that changes in pH within photoreceptors due to metabolic activity, ATP hydrolysis, regulation of proton extrusion or transport of calcium via PMCA (20) could in turn regulate calcium influx.…”
Section: Protonsmentioning
confidence: 99%